Comparative Analysis of Erosion-Corrosion in Stainless Steels: Evaluating AISI 304, AISI 316, and UB6 Across Varied Corrosive Conditions - Mesbah, Khaoula; Ouaki, Bennaceur; El Kouifat, Mohammed Khalil; Ayad, Ghassan (Zielona Góra: Uniwersytet Zielonogórski)
This study investigates the erosion-corrosion behavior of stainless steels AISI 304, AISI 316, and UB6 (AISI 904L) under various impact angles and environmental conditions (neutral, saline, and acidic). The research focuses on assessing material resistance, analyzing the influence of impact parameters and environments on degradation, and exploring the synergy between erosion and corrosion. Results show that AISI 304 exhibits the highest degradation, particularly at a 45 [degrees] impact angle in acidic conditions. AISI 316 demonstrates moderate resistance, with greater sensitivity in saline and acidic media, while UB6 shows better resistance. Experiments were conducted using a custom test bench designed at the Materials Engineering Laboratory. Statistical analysis (ANOVA) of results showed the significant effects of impact angle and environment on mass loss of chosen material for test.
Keywords: corrosive environment; corrosion; erosion-corrosion; impact angle; mass loss; stainless steel